A 28 GHz Broadband Low Noise Amplifier in a 130 nm BiCMOS Technology for 5G Applications - Kolb, Katharina; Potschka, Julian; Maiwald, Tim; Aufinger, Klaus; Dietz, Marco; Weigel, Robert (IEEE Microwave and Radar Week, 2020)
This paper presents a 28GHz broadband low noise amplifier (LNA) with a fractional bandwidth > 32 % for 5G wireless communication systems. The LNA provides a very low noise figure, a high linearity and a compact size. These properties are essential in a 5G MIMO receiver front-end. The LNA is designed in a 130 nm SiGe BiCMOS technology and provides 24 dB gain at 28 GHz with a 3 dB-bandwidth from 21.4 t 30.6 GHz. The simulated noise figure at 28GHz yields 2.18 dB. An input-referred 1 dB-compression point of -13.0 dBm is reached with a DC-power consumption of 25.1 mW <br
Keywords: 5G mobile communication; BiCMOS integrated circuits; low noise amplifier (LNA); millimeter-wave integrated circuits; noise figure; optimal matching